Prognostic value of left ventricular contractile reserve and heart rate reserve in dilated cardiomyopathy. (3rd October 2022) - Ciampi, Q; Cortigiani, L; Zagatina, A; Wierzbowska-Drabik, K; Rigo, F; Djordjevic-Dikic, A; Amor, M; Merli, E; Arbucci, R; Celutkiene, J; Gaibazzi, N; Bartolacelli, Y; et al.
Abstract: Background: Stress echocardiography (SE) allows to assess simultaneously left ventricular contractile reserve (LVCR) and heart rate reserve (HRR) in dilated cardiomyopathy (DCM). Aim: To assess the prognostic value of LVCR and HRR in DCM patients Methods: We prospectively enrolled 395 DCM patients with ejection fraction ≤40% (age 62±27 years, 270 males, 68%; ejection fraction 35±9%) referred from 9 certified laboratories, 264 with nonischemic DCM (67%) and 131 (33%) with ischemic DCM. All patients underwent clinically indicated SE. The employed stress modality was exercise (n=63), or pharmacological stress (n=332, with vasodilator, n=232; or dobutamine, n=100). LVCR was present with a rest-stress decrease ≥0.20 in wall motion score index. HRR was normal with a peak-rest value ≥1.80 with exercise or dobutamine and ≥1.22 with dipyridamole or adenosine stress. Results: New regional wall motion abnormality was present in 46 (12%), LVCR in 131 (33%) and abnormal HRR in 275 (70%) DCM patients. During a median follow-up of 950 days (interquartile range: 360–1187 days) 71 deaths occurred. Annual mortality was 10.5%/year in DCM patients with abnormal HRR (HRR−) and absence of LVCR (LVCR−), 5.4%/year in patients with either abnormal HRR or absent LVCR, and 2.5%/year in patients with normal HRR and presence of LVCR (Figure 1). At multivariable analysis, only abnormal HRR (HR: 2.952, 95% CI: 1.547–5.630, p=0.001) but not absence of LVCR (HR: 1.545, 95% CI: 0.929–2.568, p=0.094), was independent predictors of survival. Conclusion: Abnormal HRR predicts adverse prognosis in DCM patients, in addition to the presence of LV CR. Funding Acknowledgement: Type of funding sources: None.